Does parent engagement enhance children's emotional well-being in family team conference? Not a panacea for families with intimate partner violence. (November 2020) - Kim, Jangmin; Choi, Mi Jin; Trahan, Mark H.; Bellamy, Jennifer L.; Pierce, Barbara
Highlights: Children's emotional well-being increased when parents engaged actively in FTC. The positive effect of parent engagement was significant for families with no IPV. Proactive strategies to address IPV are required during FTC utilization. Strong partnerships in FTC are critical for developing safety and support plans. Abstract: In child welfare, the Family Team Conference (FTC) model is designed to develop an individualized case plan to promote children's safety, permanency, and well-being through active parent engagement and community partnerships. However, no consensus has emerged regarding whether FTC is beneficial for families with Intimate Partner Violence (IPV). This study examined the role of IPV in the association between parent engagement in FTC and children's emotional well-being. Results showed that children's emotional well-being significantly increased when both parents engaged actively in FTC as equal partners who played a leading role in collaborative decision-making. Although IPV was not directly associated with children's emotional well-being, it significantly moderated the positive association between parent engagement in FTC and children's emotional well-being. More specifically, active parent engagement did not significantly enhance children's emotional well-being when parents experienced IPV. Findings suggest that careful preparation and effective strategies to address IPV are required to ensure parents' active engagement in FTC and enhance children's emotional well-being. Strong partnerships among families, child welfare caseworkers, and service providers are critical for developing safety and support plans for families with IPV during FTC utilization.